Proceedings 1999 IEEE/RSJ International Conference on Intelligent Robots and Systems. Human and Environment Friendly Robots Wit
DOI: 10.1109/iros.1999.813065
|View full text |Cite
|
Sign up to set email alerts
|

Teaching-less robot system for finishing workpieces of various shapes using force control and computer vision

Abstract: In the case of conventional industrial robot systems, operators have to write robot-language programs for each type of workpiece. This is an onerous task, especially when each workpiece has a different shape. In this paper, we propose a teaching-less robot system for the finishing of two-dimensional workpieces of various shapes and thicknesses using force control and computer vision. The robot system does not require shape information for the workpiece to be included the CAD data or to be input by the operator… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 8 publications
0
15
0
Order By: Relevance
“…Several researches have been done on generating a tool path based on the contour of a workpiece, such as teaching method [5], [6], computer vision [7], CAD/CAM approach [2], [3], [8], and so on. A teaching method and computer vision can be used to extract the contour from an unknown workpiece and to cope with the position and orientation errors.…”
Section: Introductionmentioning
confidence: 99%
“…Several researches have been done on generating a tool path based on the contour of a workpiece, such as teaching method [5], [6], computer vision [7], CAD/CAM approach [2], [3], [8], and so on. A teaching method and computer vision can be used to extract the contour from an unknown workpiece and to cope with the position and orientation errors.…”
Section: Introductionmentioning
confidence: 99%
“…Robotic deburring requires high accuracy to track the edges of a workpiece with a consistent surface finish, which is impractical on a serial manipulator robot without a force control scheme [8]. Jinno et al [19] used computer vision path planning to design deburring and chamfering paths around planar workpieces using a monocular camera. The selected path was offset to the detected workpiece to account for the radius of the deburring tool with a known normal direction to apply force using a force controller.…”
Section: Background Of Thesismentioning
confidence: 99%
“…The selected path was offset to the detected workpiece to account for the radius of the deburring tool with a known normal direction to apply force using a force controller. The selection of the offset path and normal direction was not addressed in their study [19]. Section 3.2 of this thesis presents a literature review on computer vision path planning, but there was no solution found for selecting an offset path with force control in image-space.…”
Section: Background Of Thesismentioning
confidence: 99%
See 1 more Smart Citation
“…The surface tracking based on force guiding are studied better [7] . For example, S. Ahmad and C.N.Lee [8] studied the shape recovery of an unknown planar contour present in the robot workspace.…”
Section: Introductionmentioning
confidence: 99%